Typical Carcinoid: Cytological Diagnosis of a Case and Mimickers in Cytological Sampling Techniques with Brief Review of Literature - Singh, Shashikant; Gupta, Prajwala; Malhotra, Purnima; Bhardwaj, Minakshi; Deepak, Desh (Annals of Pathology and Laboratory Medicine, 2019)
Typical carcinoids are the most well differentiated and least aggressive of pulmonary neuroendocrine tumors. Cytologic diagnosis on trans bronchial needle aspirate (TBNA) smears is quite diagnostic; however, may be challenging on other cytologic specimens like bronchial brushings and bronchial washings. We discuss such a case of typical carcinoid in a 30 years old female.